Comparison and analysis of distributed power flow controller technology - Feng Xu; Xiaojun Ni; Mei Zheng; Qian Chen; Peng Qiu; Yi Lu (Energy Reports, 2022)
Distributed power flow controller (DPFC) can improve the power flow distribution of the power grid, overcome the power flow section excess, and enhance the carrying capacity of the power system. This paper firstly introduces three kinds of DPFCs: distributed series reactor (DSR), distributed unified power flow controller (DUPFC), and distributed static synchronous series compensator (DSSSC). According to multifaceted analysis, DSSSC is the most competitive solution in DPFCs. Then, based on the engineering application, the main wiring form, unit quantity configuration, installation method and control strategy of the DSSSC system are discussed. Finally, a simulation model with the DSSSC device is built in PSCAD/EMTDC. The simulation results prove the feasibility and effectiveness of the DSSSC.